General hospital patients' attitude towards systematic health risk behavior screening and intervention - Caroline Timm; Filipa Krolo-Wicovsky; Anika Tiede; Marie Spielmann; Beate Gaertner; Ulrich John; Jennis Freyer-Adam (BMC, 2024)
Abstract Background Systematic counseling on behavioral health risk factors (HRFs) may be suitable to promote health among general hospital patients. This study aimed to investigate the openness of patients towards systematic screening and intervention of HRFs, its relation to actual participation in a multi-behavioral intervention, and whether socio-economic characteristics, HRFs and health indicators are related to approval. Methods All 18- to 64-year-old patients hospitalized in five medical departments at the University Medicine Hospital Greifswald in Germany were asked between May and July 2022 to participate in a survey and in a subsequent pre-post intervention study. Among all eligible patients, 225 (78.9%) participated in the survey. Patients' approval of systematic screening and intervention of HRFs was assessed using five statements with a total sum score of 0-20 (i.e., scores of 0-6, 7-13, 14-20 referring to low, medium and high approval). Associations with intervention participation, socio-economic, behavioral and health-related patient characteristics were analyzed using logistic and multivariable linear regression analyses. Results The mean total approval of screening and intervention was 13.8 (SD = 4.8). Of the 125/ 73/ 16 patients with high/ medium/ low approval, 88.0%/ 78.1%/ 50.0% participated in the subsequent intervention, respectively. Approval was independent of socio-demographic and -economic characteristics and self-rated general health. Current tobacco smoking was the only HRF negatively (p = 0.02) and diabetes mellitus was the only disease positively (p = 0.01) associated with approval. Conclusion High approval of HRF screening, which was rather independent of socio-economic characteristics and worse self-rated general health, speaks in favor of proactively approaching and motivating all general hospital patients to participate in health behavior change intervention. Tobacco smokers might need higher efforts to motivate participation than non-smokers. Trial registration ClinicalTrials.gov Identifier NCT05365269 on May 9, 2022.